2011
DOI: 10.1111/j.1553-2712.2011.01042.x
|View full text |Cite
|
Sign up to set email alerts
|

Seventy-two-hour Returns May Not be a Good Indicator of Safety in the Emergency Department: A National Study

Abstract: Objectives: The objective was to measure the association between returns to an emergency department (ED) within 72 hours and resource utilization, severity of illness, mortality, and admission rate.Methods: This was a retrospective, cross-sectional analysis of ED visits using data from the National Hospital Ambulatory Medical Care Survey (NHAMCS) from 1998 to 2006. Cohorts were patients who had been seen in the ED within the past 72 hours versus those without the prior visit. A multivariate model was created t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
124
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(137 citation statements)
references
References 14 publications
(23 reference statements)
9
124
4
Order By: Relevance
“…(9) A literature review showed that similar previous studies analysed patient diagnoses and chief complaints in broad categories such as general symptoms; psychiatric; cardiovascular; ear, nose and throat; pulmonary; gastrointestinal; and dermatological conditions. (2,4,10,11) Having identified the three most common diagnoses that were the greatest risk factors in the 72-hour re-attendees group, namely heart problems, viral infection and abdominal pain, we observed changes in the most common presenting diagnosis in Singapore over the last decade. In 1994, a retrospective study (n = 166) conducted at the ED of Toa Payoh Hospital, Singapore, found the most common returning diagnosis to be asthma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(9) A literature review showed that similar previous studies analysed patient diagnoses and chief complaints in broad categories such as general symptoms; psychiatric; cardiovascular; ear, nose and throat; pulmonary; gastrointestinal; and dermatological conditions. (2,4,10,11) Having identified the three most common diagnoses that were the greatest risk factors in the 72-hour re-attendees group, namely heart problems, viral infection and abdominal pain, we observed changes in the most common presenting diagnosis in Singapore over the last decade. In 1994, a retrospective study (n = 166) conducted at the ED of Toa Payoh Hospital, Singapore, found the most common returning diagnosis to be asthma.…”
Section: Discussionmentioning
confidence: 99%
“…free medical consultation card, psychiatric issues and social issues) are known to be poor indicators for the quality of care rendered. (10,14) In the Hong Kong study, it was found that patients who return for such reasons were responsible for about 10% of unscheduled return visits. (2) Due to the dataset limitation, this patient group was not excluded in the study; therefore, we were unable to extrapolate that inadequate medical care in the preceding visit was a reason for 72-hour ED reattendance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…e674measures such as patient satisfaction and left-without-being-seen rates. [33][34][35][36] Many of these measures do not reflect physician-related clinical decision-making in the care provided to the patient and are often not directly controlled by ED physicians. Stang et al 20 recently developed evidence-based quality indicators for high-acuity pediatric conditions that can be applied to ED settings where children are seen.…”
Section: Figurementioning
confidence: 99%
“…While California HCUP can conveniently measure ED revisits, studies that have closely examined ED revisits as a marker of quality have found they are not a reliable indicator of poor care. 3 In one study of 72-hour ED return admissions, only one in 20 visits had any deviation from the standard of care or any change in outcome as a result of poor quality care during the first ED visit. 4 The reason that ED revisits are important is because in a minority of revisit admissions, there are clinically important conditions that were initially missed, such as appendicitis, acute myocardial infarction, fracture, or subarachnoid hemorrhage.…”
mentioning
confidence: 99%